2020
DOI: 10.3389/fgene.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Systems Genetics of Optic Nerve Axon Necrosis During Glaucoma

Abstract: In this study, we identify genomic regions that modulate the number of necrotic axons in optic nerves of a family of mice, some of which have severe glaucoma, and define a set of high priority positional candidate genes that modulate retinal ganglion cell (RGC) axonal degeneration. A large cohort of the BXD family were aged to greater than 13 months of age. Optic nerves from 74 strains and the DBA/2J (D2) parent were harvested, sectioned, and stained with p-phenylenediamine. Numbers of necrotic axons per optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The mechanisms underlying RGC injury during ph-IOP include: (1) Mechanical pressure on the optic disc and lamina cribrosa, which distorts the fovea, compresses RGC axons, and blocks axoplasmic transport, resulting in the activation of apoptotic and necrotic pathways; (2) decreased retinal blood perfusion, resulting in RGC ischemic injury; (3) activation of immune responses, leading to inflammatory cell infiltration that injures RGCs; and (4) other potential mechanisms [ 5 7 ]. Effective clinical options are limited, and current glaucoma treatments aim to lower ph-IOP using medications or surgery [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying RGC injury during ph-IOP include: (1) Mechanical pressure on the optic disc and lamina cribrosa, which distorts the fovea, compresses RGC axons, and blocks axoplasmic transport, resulting in the activation of apoptotic and necrotic pathways; (2) decreased retinal blood perfusion, resulting in RGC ischemic injury; (3) activation of immune responses, leading to inflammatory cell infiltration that injures RGCs; and (4) other potential mechanisms [ 5 7 ]. Effective clinical options are limited, and current glaucoma treatments aim to lower ph-IOP using medications or surgery [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the MF category, the DEGs primarily associated with protein kinase binding, protein serine/threonine kinase activity and metal ion binding. The previous study has shown that CDC42 binding protein kinase beta is associated with changes in the number of necrotic axons in the optic nerve [27] . Rho kinase, a serine/threonine protein kinase, its inhibitors reduce IOP in vivo and in vitro [28] .…”
Section: Discussionmentioning
confidence: 95%
“…The sequence is located on human 14q32.33, which has previously been identified as a potential evolutionary breakpoint ( Ruiz-Herrera et al, 2006 ; Longo et al, 2009 ). This protein has recently been identified as one of eight probable modulators of optic nerve necrosis in mice ( Stiemke et al, 2020 ). It has also been demonstrated that TMEM179 is expressed in oligodendrocyte precursor cells (OPCs), astrocytes, and neurons; and that it is found in the cortex, hippocampus, and hypothalamus of mice ( He et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%